The effect of a transient premature luteinizing hormone surge without elevated serum progesterone on in vitro fertilization outcomes in a gonadotropin-releasing hormone antagonist flexible protocol. (2nd June 2020) - Zhang, Duoduo; Zhang, Dan; Sun, Zhengyi; Deng, Chengyan; Yu, Qi; Zhen, Jingran
Abstract: During controlled ovarian stimulation, the LH rising before triggering can lead to follicular luteinizations. However, LH can be suppressed immediately and no progesterone elevation with GnRH antagonist. This study retrospectively compared fresh IVF/ICSI cycle outcomes in antagonist protocols between the group with and the group without a premature LH surge. Logistic regression models were fitted to reduce the relevant confounders. Compared between premature LH surge group and control group, the implantation rates were 12.9% (30/233) vs 25.0% (141/536), p  = .000; clinical pregnancy rates were 21.0% (25/119) vs 41.6% (119/286), p  = .000; live birth rates were17.6% (21/119) vs 29.7% (85/286), p  = .012. After adjusting for age, BMI, bFSH, and infertility factors, the adverse effects were still as pronounced for the clinical pregnancy rate (OR = 0.39, 95% CI = 0.24–0.66) and live birth rates (OR = 0.54, 95% CI = 0.32–0.93. In a GnRH antagonist flexible protocol, a transient premature LH surge which can be suppressed immediately after the initiation of antagonist without elevated serum progesterone, will cause a detrimental effect on the development of the embryo and IVF/ICSI pregnancy outcomes in fresh embryo transfer cycles.